Magnetic PDMS microparticles for biomedical and energy applications - Lima, Rui Alberto Madeira Macedo (2019)
Polydimethylsiloxane (PDMS) is one of the most widely used polymers in microfluidics. Furthermore, magnetic nanoparticles (MNPs), due their superior thermal properties, are also gaining a great interest among the industry and microfluidic scientific community. In this work, a technique based on a flow focusing principle was used to produce magnetic PDMS microparticles. A microvisualization system composed by digital video cameras and optical lenses was used to control and measure the size of the obtained microparticles. To the best of our knowledge, this is the first work that shows magnetic PDMS microparticles able to be used for both biomedical and energy applications.